A Sensitive Sensor Based on Single‐walled Carbon Nanotubes: Its Preparation, Characterization and Application in the Electrochemical Determination of Drug Clorsulon in Milk Samples. Issue 2 (24th September 2019) - Rudnicki, Konrad; Brycht, Mariola; Leniart, Andrzej; Domagała, Sławomir; Kaczmarek, Katarzyna; Kalcher, Kurt; Skrzypek, Sławomira
Abstract: Within this paper, a glassy carbon electrode modified with single‐walled carbon nanotubes (SWCNTs−GCE) was prepared, and employed for the determination of clorsulon ( Clo ), which is a frequently used veterinary drug against common liver fluke. The comprehensive topographical and electrochemical characterizations of bare GCE and SWCNTs−GCE were performed by atomic force microscopy, electrochemical impedance spectroscopy, and cyclic voltammetry. Significantly enhanced electrochemical characteristics of SWCNTs−GCE toward a ferrocyanide/ferricyanide redox couple was observed when compared to bare GCE. Further, the prepared sensor was applied for the voltammetric determination of Clo, which was electrochemically investigated for the first time in this work. Voltammetric experiments were performed using square‐wave voltammetry with optimized parameters in phosphate buffer solution, pH 6.8, which was selected as the most suitable medium for the determination of Clo . The corresponding current at approx. +1.1 V increased linearly with Clo concentration within two linear dynamic ranges of 0.75–4.00 μmol L −1 (R 2 =0.9934) and 4.00–15.00 μmol L −1 (R 2 =0.9942) with a sensitivity for the first calibration range of 0.76 μA L μmol −1, a limit of detection of 0.19 μmol L −1, and a limit of quantification of 0.64 μmol L −1 . The developed method was subsequently applied for quantitative analysis of Clo in milk samples with results proving high repeatability and recovery. Abstract :